Intrathyroidal Clear Cell Tumor of Parathyroid Origin with Review of Literature. (27th November 2016) - Pirela, Daniela; Treitl, Daniela; El Hussein, Siba; Poppiti, Robert; Mesko, Thomas; Manzano, Alex
Abstract : Water-clear cell adenoma (WCCA) of the parathyroid gland is an exceedingly rare neoplasm. To date, 17 cases have been reported in the literature, with only one of them being intrathyroidal. Here we report a case of a 34-year-old woman who presented for evaluation of a goiter and was found to have a thyroid nodule and abnormal thyroid function tests (TFT). Fine needle aspiration biopsy of the nodule revealed thyroid follicular cells without atypia and subsequent Afirma® Gene Expression Classifier (GEC) testing results were suspicious for malignancy. As a result, the patient underwent a right thyroid lobectomy and isthmusectomy. Histological sections revealed an intrathyroidal nodule consistent with a clear cell neoplasm of parathyroid origin. The histologic appearance together with the immune profile was diagnostic of WCCA, with diffuse positivity for GATA3, focal weak positivity for parathyroid hormone, and negativity for PAX8, thyroglobulin, TTF1, synaptophysin, chromogranin, and S100p. Our study focuses on the clinical presentation, current management strategies, and review of the available literature surrounding this rare diagnosis. The ultimate goal is to help endocrinologists and surgeons establish a foundational treatment plan for intrathyroidal clear cell tumor cases.